Trabalho sexual e exploração de mulheres de baixa renda na sociedade hetero-patriarcal-racista capitalista - Moreira, Fernanda Picinin (2025)
This study aimed to analyze how the exploitation related to women's productive and reproductive work in contemporary capitalist hetero-patriarchal-racist society produces and intensifies the exploitation of women's work in prostitution. To achieve this objective, we seek to discuss how reproductive work can be related to the precarious and unequal insertion of women in the labor market, as well as how it becomes functional for the continuity and reproduction of the capitalist mode of production. Thus, we understand how sex work in the context of prostitution is established as a productive activity in contemporary capitalist society, becoming a labor option for lowincome women. Likewise, we problematize the need to discuss prostitution within the scope of social, sexual, and labor rights. To this end, we used a qualitative methodology, based on interviews with two sex workers who were open to talking about their experiences and memories of themselves as workers, the context of prostitution, work and their feelings. It is also important to emphasize that listening to female sex workers made it possible to shed light on female voices that are often subjugated.